What drives her hustle? Unravelling women entrepreneurs’ satisfaction on Facebook consortia - Chakraborty Dey, Tanima; Gohain, Daisy; Gohain, Tiny Tanushree (Frontiers in Communication, 2025)
PurposeFacebook has rapidly emerged as a leading social media platform, with many women increasingly using it for entrepreneurial activities. This study aims to examine the factors having relationship with satisfaction of women entrepreneurs participating in business groups (consortiums) on Facebook in India with particular focus on socio-demographic variables, competitiveness, and association with other consortiums.MethodsFor this study, the garment sector was randomly selected, and 300 completed data were collected using the snowball sampling method. By employing binary logistic regression this study tries to examine the relationship between socio demographic variables, including time spent in Facebook consortiums, source of income, competitiveness, and association with other consortiums.ResultsThe findings disclose that higher levels of income, competitiveness, association with other consortiums have significant positive relationship with women entrepreneurs’ satisfaction within Indian context.Limitations/ImplicationsThis study contributes to literature positioning women’s digital entrepreneurship specially in an emerging economy, and also presents insights on how online consortiums could shape women entrepreneurial satisfaction. Limitations and scope of future research have been discussed to guide future studies on satisfaction of women entrepreneurs in digital ecosystems. Based on the insights, theoretical, and practical implications were discussed.